2020
DOI: 10.1103/physrevmaterials.4.094202
|View full text |Cite
|
Sign up to set email alerts
|

Correlated electron metal properties of the honeycomb ruthenate Na2RuO3

Abstract: We report the synthesis and characterization of polycrystalline Na 2 RuO 3 , a layered material in which the Ru 4+ (4d 4 configuration) form a honeycomb lattice. The optimal synthesis condition was found to produce a nearly ordered Na 2 RuO 3 (C2/c phase), as assessed from the refinement of the time-of-flight neutron powder diffraction. Magnetic susceptibility measurements reveal a large temperature-independent Pauli paramagnetism [χ 0 ∼ 1.42(2) × 10 −3 emu/mol Oe] with no evidence of magnetic ordering down to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…The oft-made assumption that single crystals are 'better' than powders is not a reliable one. 133,134 One other major challenge is polymorphism. Syntheses of Li 2 IrO 3 , for example, often do not reliably produce the target polymorph, even when a previously-successful method is followed.…”
Section: Challenges Related To Synthesismentioning
confidence: 99%
See 3 more Smart Citations
“…The oft-made assumption that single crystals are 'better' than powders is not a reliable one. 133,134 One other major challenge is polymorphism. Syntheses of Li 2 IrO 3 , for example, often do not reliably produce the target polymorph, even when a previously-successful method is followed.…”
Section: Challenges Related To Synthesismentioning
confidence: 99%
“…In 2014, Wang et al 138 reported the susceptibility of a single-crystal sample oriented with the plane of the RuO 6 layers perpendicular to (blue) or parallel to (red) a 3 T applied field. In 2020, Veiga et al 134 reported the susceptibility of a polycrystalline sample in a 1 T applied field (green; the dotted line shows an estimated intrinsic susceptibility obtained by subtracting a Curie-like impurity contribution). Recent studies of polycrystalline samples have shown that Na 2 RuO 3 is not stable in air at ambient conditions and that carefully handled samples do not display long-range magnetic order.…”
Section: Literature Examplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Even within studies focused predominantly on disordered Na 2 RuO 3 or mixtures of the ordered/disordered phase, there are conflicting reports. Some works suggest insulating behavior with long range antiferromagnetic order [21,22], while others report a paramagnetic, moderately correlated electron metal with no observable magnetic excitations [23].…”
Section: B Magnetization and Electrical Transportmentioning
confidence: 99%